Effect of the cervical and thoracic “Daoyin” training on posture and pulmonary function in patients with upper crossed syndrome: a randomized controlled trial - Yue Guo; Ming Li; Chaowei Xie; Xiaoyan Liu; Yushan Chen; Jun Yang; Yuxue Wu; Shaoqing Chen; Shizhong Wang; Jianping Lin (BMC Complementary Medicine and Therapies)
Abstract Objectives With the growing ubiquity of electronic devices, the incidence of upper crossed syndrome (UCS) is increasing every year and tends to affect younger populations. The study was designed to assess the effect of cervical and thoracic “Daoyin” training on pain, posture, pulmonary function, cervical range of motion, and emotional state in college students with UCS. Design We conducted a parallel-group randomized control study. Setting The Fujian Medical University in China. Participants 74 patients with UCS fulfilled the study requirement and were assigned to the intervention group (IG) and the control group (CG). Intervention Instructed cervical and thoracic “Daoyin” training was given to students in the IG for eight weeks, five days a week for 45 min, whereas students in the CG continued with their usual activities. Main outcome measures Primary outcomes, including forward head and shoulder angles, pain and cervical spine function, as well as secondary outcomes, such as pulmonary function, cervical range of motion and emotional state, were measured at baseline and a follow-up of 8-week. These measurements were conducted using photogrammetry, visual analog scale (VAS), Neck Disability Index (NDI), pulmonary function, cervical range of motion test and Self-rating Anxiety Scale (SAS), respectively. The statistical analysis used the change value between the baseline and the 8-week intervention measurements. Results 74 patients (IG = 37; CG = 37) were randomized. All participants were included in the analysis. There were significant differences of the change values between groups in Forward Head Angle (FHA) (d = 1.113, P < 0.001), Forward Shoulder Angle (FSA) (d = 1.052, P < 0.001), VAS (d = 0.854, P < 0.001), NDI (d = 0.754, P = 0.005), pulmonary function (Forced Expiratory Volume in 1 s/Forced Vital Capacity (FEV1/FVC) (d = 0.516, P = 0.002), maximal voluntary ventilation (MVV) (d = 0.504, P = 0.033), cervical range of motion in Left Rotation (LR) (d = 0.647, P = 0.014) and emotional state (d = 0.587, P = 0.014). No side effects were observed in this study. Conclusion Cervical and thoracic “Daoyin” training can improve the abnormal posture of head forward and round shoulders, reducing pain and anxiety, improving cervical spine function, and improving lung function to a certain extent. Trial registration ChiCTR2300072669 (20/06/2023), Prospective registration, www.chictr.org.cn .